2005
DOI: 10.1079/pns2004407
|View full text |Cite
|
Sign up to set email alerts
|

Central regulation of energy balance: inputs, outputs and leptin resistance

Abstract: The regulation of energy balance is complex and, in man, imprecise. Nevertheless, in many individuals intake and expenditure are balanced with <1% error with little or no conscious effect. Essential components of such a regulatory system are signals, leptin and insulin, that reflect the size of lipid stores. Leptin receptors signal via phosphatidylinositol 3-kinase (as do insulin receptors) and via the transcription factor signal transducer and activator of transcription-3 to activate various types of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 81 publications
5
35
1
4
Order By: Relevance
“…The flattening of the leptin curves reflects a greater increase in leptin per unit increase in percentage fat at higher levels of percentage fat. This is consistent with leptin resistance that occurs in most obese persons (22,23). Substituting height and weight, or the FIGURE 3.…”
Section: Discussionsupporting
confidence: 50%
“…The flattening of the leptin curves reflects a greater increase in leptin per unit increase in percentage fat at higher levels of percentage fat. This is consistent with leptin resistance that occurs in most obese persons (22,23). Substituting height and weight, or the FIGURE 3.…”
Section: Discussionsupporting
confidence: 50%
“…Recent work has linked leptin resistance to both reduced leptin transport across the blood brain barrier as well as reduced leptin signaling (Arch, 2005;Banks et al, 2004;Banks and Farrell, 2003;Feng, 2006;Steinberg et al, 2006). However, the presence of leptin resistance in our study population would most likely serve to negatively confound our analysis, masking an even more robust association between higher leptin levels and reduced likelihood of cognitive decline.…”
Section: Discussionmentioning
confidence: 88%
“…Mature adipocytes produce adiponectin, which increases insulin sensitivity, glucose uptake, fatty acid oxidation, and anti-inflammatory effects in hormone-stimulated lipolysis [25] . To prevent lipid accumulation in adipose tissue, adipocytes secrete leptin to regulate food intake and fatty acid oxidation contacted with brain [26] . The plasma concentration of adipose tissues and endocrine hormones revealed that GCBE treatment reduced leptin concentrations and inversely increased adiponectin, in a dose dependent manner.…”
Section: Discussionmentioning
confidence: 99%